Characterization of Dielectric Containers used in Improvised Explosive Devices using Radar Cross-Section techniques (2019)
This document presents the experimental development using an M-Sequence radar, the response of the Radar Cross-Section (RCS) for Improvised Explosive Devices (IED) used in Colombia. The construction and manipulation of these artifacts were carried out under the supervision of the Army. These artifacts are built mostly with glass bottles, plastic containers, empty containers or plastic pipelines. Additionally, the IED have cables, batteries, insulating tape, detonator and some activation method (syringes, clothes hooks or whatever activation type). The samples were divided into three different groups to determine the characteristics of discrimination. The first group called clutter is made up of empty containers. The second group called IED with air inside, the empty container of the first group, but with some modifications, cables, batteries, detonator and activation method were added, this group does not contain any material inside, only air. Finally, the third group called IED with substitute material is the same artifact of the second group, but inside it has a synthetic material that has the same electrical behavior as the ANFO (from the English Ammonium Nitrate-Fuel Oil). The separation in these three groups allowed observing the difference of magnitude of the SCR that exists between them. In some frequencies the response of the RCS is divided into two groups, the first group corresponds to the clutters and the second group corresponds to the IED with air and substitute material inside it, and in others, the RCS of each group is not differentiated. These results were validated with a test using a Vector Network Analyzer (VNA) and the same radar of the first test with a different configuration. The validation allowed us to verify that regardless of whether a VNA or radar is used, the behavior for the three groups is similar to the first test.